PPI-responsive esophageal eosinophilia cannot be distinguished from eosinophilic esophagitis by endoscopic signs. Issue 5 (May 2015) - Warners, Marijn J.; van Rhijn, Bram D.; Curvers, Wouter L.; Smout, Andreas J.P.M.; Bredenoord, Albert J.
Abstract : Background: Eosinophilic esophagitis (EoE) is a chronic antigen-mediated disease histologically characterized by eosinophil-predominant inflammation. One-third of patients respond to proton pump inhibitor (PPI) treatment; this group is identified as having PPI-responsive esophageal eosinophilia (PPI-REE). If we could predict the response to PPIs on the basis of endoscopic signs, futile treatment efforts and additional endoscopies to assess treatment response can be prevented. Objective: To determine whether endoscopic signs can distinguish PPI-REE from EoE. Methods: Endoscopic images of 30 EoE and 30 PPI-REE patients were included. Baseline characteristics were compared between groups. Complete clinical remission after a PPI trial for at least 8 weeks was classified as PPI-REE. Per patient, at least three depersonalized images were incorporated into a slideshow. These images were scored by two experienced endoscopists according to a validated classification system. Results: Characteristics were highly comparable between EoE and PPI-REE patients. Endoscopic signs were similar and did not enable differentiation between EoE and PPI-REE [presence of: rings ( P =0.893), white exudates (P =0.209), furrows ( P =0.371), edema ( P =0.554), crepe paper esophagus ( P =1.000), and strictures ( P =0.071)]. Conclusion: Endoscopic signs at baseline endoscopy cannot distinguish EoE from PPI-REE before a PPI trial; the demographic and clinical characteristics in both groups are similar. Endoscopic features do not enable differentiation between PPI-REE and EoE.